PROPOSED IMPROVEMENTS TO INCREASE CUSTOMER REPURCHASE INTENTIONS AT DEPARTMENT STORE X - Budiono, Fernand Amadeo; Sitorus, Hotna Marina Rosaly (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The retail sector is one of the most significant sectors of the Indonesian economy, where according to the Minister of Trade, it contributed 53,56% of GDP in the first quarter of 2022. One example of a retail business in Indonesia is Department Store X, located in Bandung City, one of Indonesia’s largest retail markets. However, since 2017, the number of visitors and sales there has stagnated, and has been pretty much the same for the last 6-7 years, despite rising costs of labor and product procurement, which is very concerning for the store’s longevity. The objective of this research is to identify and analyze what key factors effect customer repurchase intentions at Bandung City department stores such as Department Store X, as it was found that the problem was caused by low customer retention. Many old customers were hesitant or unwilling to shop in Department Store X again. This research itself aims to study the effect of several independent variables, including advertising and promotions, store environment & layout, service quality, product diversity, and location as well as several mediating variables, including customer satisfaction, perceived value, and emotions/feelings in the store on the dependent variable of customer repurchase intentions. The methodology used in this research involved using a questionnaire with a convenience sampling technique for data collection and PLS-SEM (Partial Least Squares Structural Equation Modelling) for data processing. The results of this research found that product diversity, location, and customer satisfaction had a positive and significant effect on repurchase intention.